Key out of time - Norton, Andre. (Gregg Press, 1978)
Ross Murdock, Gordon Ashe, and other members of the Terran settlement team travel back in time to investigate a civilization that once flourished on Hawaika, a world of shallow seas and archipelagoes.
Reprint of the ed. published by Ace Books, New York.
Ross Murdock, Gordon Ashe, and other members of the Terran settlement team travel back in time to investigate a civilization that once flourished on Hawaika, a world of shallow seas and archipelagoes.